A poor sales pitch? The European citizens' initiative and attitudes toward the EU in Germany and the UK. Issue 3 (2nd July 2016) - Gherghina, Sergiu; Groh, Adriana
ABSTRACT: Earlier research about the European citizens' initiative (ECI) focused on its normative value, functioning mechanisms, and the extent to which citizens are willing to engage with it. So far, little efforts were made to investigate whether the ECI has an effect on citizens' attitudes. This article provides an empirical assessment about how knowledge about the ECI and the willingness to use it may enhance a positive image about the European Union (EU). The explanatory power of these two variables is tested against other determinants identified in the literature as sources of a positive image about the EU: democratic performance, perception of representation, the pursuit of interests, and citizenship. The study draws on an original data set collected through a web-survey at the beginning of 2015. Results indicate a limited and sometimes counter-intuitive effect of the ECI on the image about the EU with several implications for the future of this participatory tool.